Diaspora engagement for development: challenges and options for Guyana - Corbin, Hisakhana Pahoona; Aragón, Luis Eduardo (Geografares, 2017)
Having lost 60.8% of its population to migration and 93% of graduates with higher education by 2011, diaspora engagement may not be an option for Guyana in the future. Based on data collected from multiple sources and a review of the existent literature on diaspora engagement for development across the world, this paper seeks to unveil potentials and challenges that Guyana may face as it seeks to engage its diaspora for development. In addition to defining the Guyanese diaspora and reviewing interventions currently adopted by the government of Guyana for diaspora engagement, this paper also sheds light on concerns by Guyanese in the diaspora given the current political and socioeconomic conditions in Guyana and the challenges they face as efforts are made to contribute to Guyana´s development. Further, a review of interventions implemented by other countries around the world is presented with the focus of widening the options for Guyana. Keywords: Diaspora, Guyana, development.